Absolute scattering length density profile of liposome bilayers obtained by SAXS combined with GIXOS: a tool to determine model biomembrane structure - Harvey, Richard D. (2024)
Lipid membranes play an essential role in biology, acting as host matrices for biomolecules like proteins and facilitating their functions. Their structures and structural responses to physiologically relevant interactions (i.e. with membrane proteins) provide key information for understanding biophysical mechanisms. Hence, there is a crucial need of methods to understand the effects of membrane host molecules on the lipid bilayer structure. Here, a purely experimental method is presented for obtaining the absolute scattering length density profile and the area per lipid of liposomal bilayers, by aiding the analysis of small-angle X-ray scattering (SAXS) data with the volume of bare headgroups obtained from grazing-incidence X-ray off-specular scattering (GIXOS) data of monolayers of the same model membrane lipid composition. The GIXOS data experimentally demonstrate that the variation of the bare headgroup volume upon change in lipid packing density is small enough to allow its usage as a reference value without knowing the lipid packing stage in a bilayer. This approach also has the advantage that the reference volume is obtained in the same aqueous environment as used for the model membrane bilayers. The validity of this method is demonstrated using several typical membrane compositions, as well as one example of a phospholipid membrane with an incorporated transmembrane peptide. This methodology allows us to obtain absolute scale rather than relative scale values using solely X-ray-based instrumentation, retaining a similar resolution to SAXS experiments. The method presented has high potential for understanding the structural effects of membrane proteins on the biomembrane structure.